Réponses

2014-04-11T15:48:44+02:00
1) Q = (2+x)(2x+5)-(2-x)(2+x)
Q = 4x + 10 + 2x² + 5x - (4 + 2x - 2x - x²)
Q = 4x + 10 + 2x² + 5x -4 - 2x + 2x + x²
Q = 3x² + 9x + 6

2)
Q = (2+x)(2x+5)-(2-x)(2+x)
Q = (2 + x) [(2x + 5) - (2 - x)]
Q = (2 + x) (2x + 5 - 2 +x)
Q = (2 + x) (3x + 3)

3) Q = 0

(2 + x) (3x + 3) = 0
Si un produit de facteurs est nul alors l'un des deux facteurs est nul :
2 + x = 0
2 - 2 +x = 0- 2
x = -2
OU
3x + 3 = 0
3x + 3 - 3 = 0 - 3
3x = -3
x = -3/3
x = -1

J'espère t'avoir été utile :)